Effect of dry period therapy on prevalence of mastitis in buffaloes in Haryana - ASHOK BOORA; SARITA YADAV; PARVEENA DEVI; ANIL KUMAR; INDERJEET SINGH; V P CHAHAL (Indian Journal of Animal Sciences, 2020)
The study attempts to compute the effect of dry period therapy on occurrence of mastitis in buffaloes with the help of control (164 buffaloes) and treatment (330 buffaloes) groups at different stages as per disease diagnostic protocol. The data pertains to the year 2018-19. The study concludes overall prevalence of SCM at dry-off was 83.81% and at 5 days postpartum was 38.87% at animal level. In treatment group, prevalence of SCM was 89.70% and 28.48% at dry-off and 5 days postpartum respectively whereas 73.17% and 62.8% in control group. The most prevalent udder pathogens isolated from composite milk samples at dry off were coagulase-negative Staphylococcus, representing 41.29% of all recovered isolates followed by other gram positive, Streptococcus spp. Overall, 63.02% of buffaloes with IMI were cured during the dry period. Buffaloes receiving dry period therapy were 3.85 times more likely to cure.